A novel IRF6 gene mutation impacting the regulation of TGFβ2-AS1 in the TGFβ pathway: A mechanism in the development of Van der Woude syndrome - Zhao, Zhiyang; Cui, Renjie; Chi, Haoshu; Wan, Teng; Ma, Duan; Zhang, Jin; Cai, Ming (Frontiers in Genetics, 2024)
Several mutations in the IRF6 gene have been identified as a causative link to VWS. In this investigation, whole-exome sequencing (WES) and Sanger sequencing of a three-generation pedigree with an autosomal-dominant inheritance pattern affected by VWS identified a unique stop-gain mutation-c.748C>T:p.R250X-in the IRF6 gene that co-segregated exclusively with the disease phenotype. Immunofluorescence analysis revealed that the IRF6-p.R250X mutation predominantly shifted its localization from the nucleus to the cytoplasm. WES and protein interaction analyses were conducted to understand this mutation's role in the pathogenesis of VWS. Using LC-MS/MS, we found that this mutation led to a reduction in the binding of IRF6 to histone modification-associated proteins (NAA10, SNRPN, NAP1L1). Furthermore, RNA-seq results show that the mutation resulted in a downregulation of TGFβ2-AS1 expression. The findings highlight the mutation's influence on TGFβ2-AS1 and its subsequent effects on the phosphorylation of SMAD2/3, which are critical in maxillofacial development, particularly the palate. These insights contribute to a deeper understanding of VWS's molecular underpinnings and might inform future therapeutic strategies.